Development of Pocket Book of Tissue Culture Based on Case Method - Harahap, Fauziyah; Sihombing, Josephine Gloria Margareth; Suriani, Cicik; Nusyirwan, Nusyirwan; Edi, Syahmi; Daulae, Abdul Hakim; Nursamsu, Nursamsu (UNIVERSITAS ISLAM NEGERI RADEN INTAN LAMPUNG, 2023)
The use of pocket book as a learning media is still limited. This will make it difficult for students to understand the material. The purpose of this research was to determine the feasibility results of tissue culture pocket book, the level of product feasibility through responses from lecturers, students and to see the effectiveness of tissue culture pocket book products especially in tool sterilization and in vitro propagation topics. The research method uses R&D with 4D models from Thiagrajaan. The results of the needs analysis showed that 66,7% of students had difficulty in understanding the material of tool sterilization and in vitro propagation. In curriculum analysis using the KKNI curriculum. The feasibility level of the assessment product from media experts obtained the criteria